Rocket meezaile or musnoai siaray - Dr muhammad gulistan (Ferozesons; Lahore, 2011)
Rocket, Meezaile Aur Musnoai Siaray explores the fascinating world of modern warfare technology, delving into the development and impact of rockets, missiles, and artificial satellites.